2019
DOI: 10.1093/nar/gkz202
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of HIV-1 Gag/Gag-Pol frameshifting by tRNA abundance

Abstract: A hallmark of translation in human immunodeficiency virus type 1 (HIV-1) is a –1 programmed ribosome frameshifting event that produces the Gag-Pol fusion polyprotein. The constant Gag to Gag-Pol ratio is essential for the virion structure and infectivity. Here we show that the frameshifting efficiency is modulated by Leu-tRNA Leu that reads the UUA codon at the mRNA slippery site. This tRNA Leu isoacceptor is particularly rare in human cell lines derived from T-lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 78 publications
3
35
0
Order By: Relevance
“…(i) slippage of the single P-site tRNA when the A site remains vacant, or (ii) frameshifting of both P-site and A-site tRNAs when two tRNAs are bound to the ribosome (Caliskan et al, 2017;Korniy et al, 2019). Our finding that the dnaX FSS slows the rate of ribosome translocation by ~10-fold is also in excellent agreement with a number of previous reports (Caliskan et al, 2017;Chen et al, 2014;Choi et al, 2020;Kim et al, 2014;Kim and Tinoco, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…(i) slippage of the single P-site tRNA when the A site remains vacant, or (ii) frameshifting of both P-site and A-site tRNAs when two tRNAs are bound to the ribosome (Caliskan et al, 2017;Korniy et al, 2019). Our finding that the dnaX FSS slows the rate of ribosome translocation by ~10-fold is also in excellent agreement with a number of previous reports (Caliskan et al, 2017;Chen et al, 2014;Choi et al, 2020;Kim et al, 2014;Kim and Tinoco, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…1) that in combination with the slippery sequence UUUUUUA, induces -1 PRF with 5-10% efficiency to produce the Gag-Pol polyprotein. mRNAs containing the slippery sequence and HIV FSS undergo frameshifting in bacterial (E. coli) ribosomes in vitro and in vivo at frequencies comparable to those observed for HIV frameshifting in eukaryotic translation systems (Brunelle et al, 1999;Korniy et al, 2019;Leger et al, 2004;Mazauric et al, 2009). The FSS from HIV can be studied in E. coli, analogous to -1 PRF on mRNA derived from another eukaryotic virus (avian infectious bronchitis virus, IBV) that could also be reconstituted in the E. coli translation system (Caliskan et al, 2014) suggesting a common mechanism of frameshifting and ribosomal stalling induced by FSS in bacteria and eukaryotes.…”
Section: Resultsmentioning
confidence: 79%
“…Kinetic analysis shows that -1PRF in HIV-1 proceeds via the same two routes as previously described for IBV 1a/1b and E. coli dnaX mRNAs (Fig. 2) [69]. Intriguingly, we found that the two routes depend on the availability of Leu-tRNA Leu(UAA) to read the UUA codon of the SS1 (Fig.…”
Section: Frameshifting Elements In the Mrnasupporting
confidence: 80%
“…When SS1 is functional and pSS2 harbors the C 5 U mutation, the overall -1 frameshifting efficiency remains unchanged but a significant amount of -2 frameshifting is observed. Most importantly, when SS1 is dysfunctional, the C 5 U mutation in pSS2 can restore about 70% of the wildtype -1PRF efficiency, which might be enough to sustain the viral lifecycle [69]. Interestingly, HIV-1 is not the only virus which develops an alternative slippery site in response to antiviral treatment.…”
Section: Appearance Of Potential Slippery Sites In Viruses Upon Antivmentioning
confidence: 99%
“…Ribosome stalling due to limited tRNA availability has the potential to lead to slippage of the ribosome 82,83 and contributes to nonprogrammed frameshifting in huntingtin 84 . Availability of tRNAs decoding slippery site codons have been shown to influence HIV gag-pol frameshifting efficiency 85 , and HIV-1 itself has the ability to modulate the tRNA pool of the host cell 86 . Our observation that limited tRNA availability in the codons leading up to the slippery site progressively contributes to PRF efficiency is in line with these data and expands the notion of an influence of the tRNA pool on frameshifting beyond the slippery site codons and individual PRF events.…”
Section: Discussionmentioning
confidence: 99%